Implementation of Local Regulations Concerning Market Charges and Problems in Practice - Harti Harti (Law Development Journal, 2020)
This research raises a problem regarding the Retribution for Markets, Wholesale Markets and Shops controlled by the Demak Regency Government in Bintoro Market, Demak Regency.This research was conducted with a qualitative approach. The research was conducted at the Demak Regency DPRD, Demak Regency Legislation Section, Demak Regency DPKKD Office. Office of the Department of Industry, Trade, Cooperatives, MSMEs, Regional Regional I Pasat UPTD Offices, Demak District Civil Service Police Unit and Bintoro market. Data collection methods used were interviews and documentation. The data analysis method is descriptive and the analysis used is qualitative.The results showed that the implementation was not going well. This can be seen in the many articles in Regional Regulation Number 2 of 1999 concerning Retribution for Markets, Wholesale Markets and Shops controlled by the Demak Regency Government which are not applied in the field besides that the collection of field contribution rates is not in accordance with the provisions stipulated in Regional Regulation Number 2 years 1999 concerning Retribution for Markets, Wholesale Markets and Shops controlled by the Demak Regency Government. In the implementation of Regional Regulation Number 2 of 1999 concerning Retribution for Markets, Wholesale Markets and Shops which are controlled by the Demak Regency Government, there are supporting and inhibiting factors.Keywords: Retribution; Market; Wholesale markets and shops